ANALISIS IBS TERHADAP PENYERAPAN TENAGA KERJA DI KABUPATENASAHAN - Veni Oktapiani Putri; Muhammad Al Fathan; Hindun Neni Sari Pasaribu; Deni Novianti (Niagawan, 2020)
One indicator to assess the success of a country's economic development is seen from the employment opportunities created. But in reality the labor absorbed is still not able to overcome unemployment. Major development will help overcome the problem of unemployment. This research was obtained through secondary data. The purpose of this research is to analyze the influence of large and medium industries on the absorption of labor in the Asahan district in 2017. The results obtained in this study are stated that the large medium industries in the Asahan district can be said to be weak in labor absorption.